Combined External Coating And Cathodic Protection Assessment Techniques ? A Case Study For A Pipeline In West Africa - Summary - Neil Webb; Brian Wyatt; Marcel Roche; John Thirkettle (The Southern African Institute of Mining and Metallurgy, 2006)
Recent developments in survey techniques and measuring equipment now allow for an accurate assessment of external coating condition and cathodic protection performance. These developments build on 20 years of experience of using Direct Current Voltage Gradient (DCVG) and Close Interval Potential Survey (CIPS) methods. The techniques use the latest advances in measurement systems coupled to a bespoke data processing system. The paper describes tests and trial surveys carried out on a hydrocarbon transmission pipeline in West Africa during 2005. The survey works described and conclusions drawn are from the data collected. Of particular interest are the apparent capacitance effects which are thought to occur under disbonded coating and the characteristics that these may show on the integrated CIPS and recorded DCVG profiles. This paper was originally presented at the Cefracor conference in Aix, France, in June 2006 The pipeline was originally installed on a phased basis between 1989 and 1994. The external coatings were three layer polyethylene factory coating and shrink sleeve field joint coating. An impressed current cathodic protection system was installed. The pipeline has subsequently been affected by disbondment of the coatings. It was a primary objective of the trials to attempt to identify such affected areas. In addition to a technically detailed account of the survey works undertaken and the results obtained the authors will consider the practical and commercial aspects of these surveys with input that provides a perspective from the specifier, pipeline surveyor, pipeline operations personnel and the pipeline owner. It is intended that the data presented will provide greater awareness of the benefits and limitations of the techniques used and their role for both stand-alone interpretation and the integration of the survey information with other inspection methods used for external corrosion assessment. The application of the described techniques is well developed and proven to locate and characterise through?coating defects and to provide a full audit of cathodic protection status. However, the possibility of the techniques being able to indicate disbonded coating is unproven and further tests and trials are planned which may allow a greater understanding of the electrical characteristics which are believed to be associated with disbonded coatings which may or may not be filled with an electrolyte. Further work is currently planned in West Africa, South Africa and Scotland in order to improve the understanding of this technique and to determine if the reported indications do actually represent a method of locating disbonded coatings. Keywords: External Coating, Cathodic Protection, DCVG, CIPS, corrosion assessment.